A precarização do trabalho dos enfermeiros no Amapá e a resistência sindical: projetos políticos educativos - Martins, Carlos Rinaldo Nogueira (2013)
This study has its theoretical-methodological epistemological basis materialized in Marxism. It retrieves the debate on the work of nurses and union resistance in the state of Amapá. Takes the view that with the advent of the neoliberal project in Brazil there was an intense precariousness of this profession, whose momentum was with the change in national policies related to health back in the Collor government. It shows that this process of precariousness enhanced the construction of a combative and socialist trade union, the workers\' resistance expression to the changes in their working conditions. It perceives that there is a precariousness process rapidly going all health categories, particularly in nursing. We believe that workers\' resistance, manifested in the organization and trade union struggle, is a political process of educational nature aimed at training the consciousness of workers in the sector about their condition of exploitation and the need to overcome this relationship.